Mobile app for unlimited saving and organisation of Reddit posts - Pang, Shi Song (Nanyang Technological University, 2023)
This report aims to enhance the post saving experience of all Reddit mobile users. This is achieved by creating a Reddit post saving mobile app solution, Keppit. Keppit will have additional features for saving of Reddit posts such as unlimited saves, search, and tagging.